2021
DOI: 10.1016/j.crneur.2021.100007
|View full text |Cite
|
Sign up to set email alerts
|

Ion-channel regulation of response decorrelation in a heterogeneous multi-scale model of the dentate gyrus

Abstract: Heterogeneities in biological neural circuits manifest in afferent connectivity as well as in local-circuit components such as neuronal excitability, neural structure and local synaptic strengths. The expression of adult neurogenesis in the dentate gyrus (DG) amplifies local-circuit heterogeneities and guides heterogeneities in afferent connectivity. How do neurons and their networks endowed with these distinct forms of heterogeneities respond to perturbations to individual ion channels, which are known to cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 121 publications
(260 reference statements)
3
37
0
Order By: Relevance
“…Although our study focused on four subtypes of ion channels, future studies could extend such analyses to other ion channels, including calcium‐activated potassium channels, voltage‐gated calcium channels, and other sodium and potassium channels in DG granule cells. Based on earlier computational predictions in DG granule cells (Beining et al, 2017 ; Mishra & Narayanan, 2019 , 2021 ), and on electrophysiological observations here, we postulate that the incorporation of additional channels to the analyses would further increase the degrees of freedom available to the neuron in maintaining similar function.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…Although our study focused on four subtypes of ion channels, future studies could extend such analyses to other ion channels, including calcium‐activated potassium channels, voltage‐gated calcium channels, and other sodium and potassium channels in DG granule cells. Based on earlier computational predictions in DG granule cells (Beining et al, 2017 ; Mishra & Narayanan, 2019 , 2021 ), and on electrophysiological observations here, we postulate that the incorporation of additional channels to the analyses would further increase the degrees of freedom available to the neuron in maintaining similar function.…”
Section: Discussionsupporting
confidence: 60%
“…This implies that, in systems expressing degeneracy, perturbation of any single structural component would elicit variable impact on functional outcomes. Consistent with this general framework, prior computational studies, involving ion‐channel knockouts or perturbations, have revealed important testable predictions that point to the expression of ion‐channel degeneracy in the emergence of cellular‐scale function (Basak & Narayanan, 2018 , 2020 ; Beining et al, 2017 ; Drion et al, 2015 ; Jain & Narayanan, 2020 ; Marder, 2011 ; Marder & Goaillard, 2006 ; Mishra & Narayanan, 2019 , 2021 ; Mittal & Narayanan, 2018 ; O'Leary, 2018 ; Onasch & Gjorgjieva, 2020 ; Rathour & Narayanan, 2014 ): Knocking out or perturbing any single ion channel altered multiple cellular‐scale physiological measurements, and any specific cellular‐scale physiological measurement was altered by knocking out or perturbing several ion channels; and The impact of blocking individual ion channels on cellular‐scale measurements is variable. Specifically, the expression of ion‐channel degeneracy translates to differential expression of individual ion‐channels in different neurons of the same subtype.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations